Effect of solvent and dispersant on the bundle dissociation of single-walled carbon nanotube - COLEMAN, JONATHAN; BLAU, WERNER; GIORDANI, SILVIA; DRURY, ANNA (My University, 2005)
Single-wall carbon nanotubes (SWCNT) are severely restricted in their applications, as they exist in rope-like bundles. Recently, J. Coleman et al. demonstrated a spectroscopic method to monitor bundle dissociation in low concentration NT-polymer composites.1 The method relies on the measurement of the ratio of free-polymer to the nanotube-bound polymer in the SWCNT-polymer solutions via luminescent spectroscopy. A theory has been developed to transform this data into the bundle surface area, which is of course related to the bundle size. This method clearly shows that individual, isolated SWCNT are stable in low concentration dispersions. The main aim of this work is to better understanding of the physics behind polymer ? SWCNT interactions, the binding scheme, and the magnitude of the polymer ? SWCNT binding energy. In an effort to broaden the understanding of the physical processes governing the NT de-bundling a wide range of suitable polymers and short-chain molecules have been examined. We found a strong dependence of the concentration at which individual NTs become stable with the nature of the dispersant molecule
PUBLISHED
Keywords: Single-wall carbon nanotubes